2005
DOI: 10.1038/sj.npp.1300918
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Self-Administration Reduces Excitatory Responses in the Mouse Nucleus Accumbens Shell

Abstract: Drugs of abuse affect behavior by altering neuronal communication within the brain. Previous research examining the effects of intraperitoneally administered cocaine has revealed that cocaine alters excitatory glutamatergic signaling, both directly through regulation of synaptic function, and indirectly through regulation of cellular excitability in areas of the drug reward circuitry such as the nucleus accumbens (NAcc) and ventral tegmental area. We have now extended these findings by testing the hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 45 publications
3
44
0
Order By: Relevance
“…For example, prolonged cocaine treatment (but not following a single injection) decreases the AMPA/NMDA receptor ratio in the NAc shell (Thomas et al, 2001). In addition, cocaine self-administration produces a postsynaptic decrease in the AMPA receptormediated fEPSP (Schramm-Sapyta et al, 2006). Finally, many studies have demonstrated changes in glutamate receptor subunit levels in the NAc following exposure to either cocaine or amphetamine (Lu et al, 1997 Acute amphetamine alters j-opioid function Y Xia et al Churchill et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prolonged cocaine treatment (but not following a single injection) decreases the AMPA/NMDA receptor ratio in the NAc shell (Thomas et al, 2001). In addition, cocaine self-administration produces a postsynaptic decrease in the AMPA receptormediated fEPSP (Schramm-Sapyta et al, 2006). Finally, many studies have demonstrated changes in glutamate receptor subunit levels in the NAc following exposure to either cocaine or amphetamine (Lu et al, 1997 Acute amphetamine alters j-opioid function Y Xia et al Churchill et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…One problem with performing intravenous drug self-administration studies in the mouse is the technical difficulty of maintaining catheter patency. Attrition rates in these experiments are high and can reach 40% or higher [10][11][12][13][14][15] . Another general problem with drug self-administration is discerning which pharmacologically-induced effects of the reinforcer produce specific behaviors.…”
Section: Introductionmentioning
confidence: 86%
“…The maintenance or lasting expression of behavioral sensitization to cocaine is, however, dependent upon the ventral striatum, and upon NAc glutamate transmission in particular (Bell et al, 2000;Pierce et al, 1996;Vanderschuren and Kalivas, 2000). Plasticity of NAc glutamatergic synapses has been associated with both cocaine sensitization (Brebner et al, 2005;Goto and Grace, 2005;Thomas et al, 2001;Yao et al, 2004) and cocaine-seeking behaviors (Martin et al, 2006;Schramm-Sapyta et al, 2006). CB 1 receptors are functionally expressed on glutamatergic axon terminals onto NAc output neurons (Robbe et al, 2001), and cocaine has been reported to alter the plasticity of these synapses (Fourgeaud et al, 2004).…”
Section: Possible Sites and Mechanism Of Actionmentioning
confidence: 99%
“…Behavioral sensitization to cocaine or amphetamine has been correlated to the expression and occlusion of longterm depression (LTD) of excitatory synaptic transmission in the NAc (Thomas et al, 2001;Brebner et al, 2005). It was also recently reported that excitatory neurotransmission was reduced (Schramm-Sapyta et al, 2006) and LTD was abolished (Martin et al, 2006) in the NAc after animals were trained to self-administer cocaine, but not following noncontingent cocaine administration.…”
Section: Introductionmentioning
confidence: 99%